Robust order representation is required for backward recall in the Corsi blocks task - Higo, Katsuki; Minamoto, Takehiro; Ikeda, Takashi; Osaka, Mariko (Frontiers in Psychology, 2014)
The storage and processing of spatial information is done by spatial working memory. To measure spatial working memory, the Corsi blocks task, which separates the memory into two types, forward and backward, is often used. Although it had been thought that backward recall requires more of the executive function than forward recall, some studies have shown otherwise. Here, we focused on the spatial and sequential aspects of the Corsi blocks task to investigate cognitive processes by dissociating forward and backward recall. We used a dual task method (serial articulatory suppression or spatial tapping as the secondary task) and analyzed two kinds of errors (position error and order error) to investigate cognitive performance during the forward and backward recall. We ran two experiments: in experiment 1, we employed the standard Corsi blocks task, and in experiment 2, we employed the modified Corsi blocks task in order to prevent verbal strategies. We found that spatial tapping affected both forward and backward recall, while serial articulatory suppression increased the number of order errors in the backward condition. These results indicate that stronger order representation is required for backward recall in the Corsi blocks task.